The Influence of Financial Literacy and Digital Payment Use towards MSMEs Performance (Case Study : IEC UNSRAT) - Rumengan, Sheren; Tulung, Joy Elly; Pandowo, Merinda H. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study aim to analyze The Influence of Financial Literacy and Digital Payment Use towards MSMEs Performance simultaneously or partially. The research variables consist of X1 is Financial Literacy, X2 is Digital Payment Use, and Y is MSMEs Performance. Research data is primary data, obtained from the resuls of the distribution of questionnaires design with likert scale. The sample of this research was all of the MSME merchants at IEC (Innovation and Entrepreneurship Center) Unsrat, with the total sample size consisted of 30 merchants or respondents. The test instruments using Validity and Reliability Test using SPSS 29. Technique analysis using Multiple Regression Analysis, Classical Assumption Test (Normality, Heteroscedasticity and Multicollinearity Test), Hypothesis Test (t-Test and F-Test). The result showed that Financial Literacy has significant influence towards MSMEs Performance, as well as Digital Paayment Use also significantly influence MSMEs Performance . And both Financial Literacy and Digital Payment Use have a positive influence towards MSMEs Performance.